The Effect of Nitrate as a Radical Scavenger for the Removal of Humic Acid from Aqueous Solutions by Electron Beam Irradiation - Mohammad Taghi Ghaneian; Mohammad Hassan Ehrampoush; Tahereh Jasemizad; Monireh Kheirkha; Reza Amraei; Fatemeh Sahlabadi (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Humic acids have adverse effects on the water quality, then should be removed from water resources. The aim of this study was to evaluate the effect of nitrate as a radical scavenger for removal of humic acid from aqueous solutions by electron beam irradiation. Materials and Methods: In this study, after preparation of stock humic acid solution in alkaline condition, different concentrations of humic acid (10, 25 and 50 mg/l) were prepared. Different concentrations of nitrate (25, 50 and 100 mg/l) added to humic acid samples and then absorption of samples was measured at 254 nm by using UV-Vis spectrophotometer before and after the electron beam irradiation. This study has done at pH= 8 and at different electron beam adsorbed dose of 1, 3, 6, 9 and 15 kGy. Results: The results of this study showed that the increasing of adsorbed dose from 1 to 15 kGy, the removal efficiency of humic acid also increased. By increasing of nitrate concentration from 25 to 100 mg/l, the removal efficiency of humic acid has decreased from 43.8% to 36.6% and nitrate acts as a radical scavenger. By increasing of humic acid concentration from 10 to 50mg/l, removal efficiency decreased in all adsorbed doses. Kinetic analysis of our results showed that the results well fitted with the second - order reaction. Conclusion: We can conclude from this study that electron beam irradiation could be a useful process for the treatment of natural organic matter (humic acid) from surface waters.